Effect of graphene content on the tribological and corrosion behavior of high-speed-laser-clad high-entropy-alloy composite coatings - Yu, Jiangtong; Sun, Wenlei; Xie, Lei; Huang, Yong; Huang, Haibo (Tribology international, 2025)
To repair oil drill pipe joints that have failed owing to dry wear and tribocorrosion, graphene-reinforced CoCrFeMo0.5NiTi0.5 high-entropy alloy composite coatings (HEACCs) were developed through high-speed laser cladding. The HEACC containing 1.5 wt% graphene exhibited dry wear and tribocorrosion rates that were 59.18 % and 32.20 % of those observed in the high-entropy alloy coating, respectively. The HEACC exhibited a corrosion current density of 2.475 × 10−7 A/cm2. The HEACC containing 1.5 wt% graphene underwent progressive damage during dry wear owing to the combined effects of abrasive wear, which created furrows; adhesive wear, which led to flaking; and oxidative wear, which formed oxide layers. During tribocorrosion, chloride ions exacerbated surface damage caused by hard abrasives and asperities, intensifying corrosive–abrasive wear interactions. ●Composite coatings of graphene-reinforced high-entropy alloys were prepared via high-speed laser cladding.●The tribocorrosion rate of the HEACC can reach 2.720 µm3·N−1·mm−1, which is only 32.20 % of that of the HEA.●The influence of the graphene content on the tribocorrosion performance of HEACCs was investigated.●The corrosion current density of the HEACC reached about an order of magnitude smaller than that of the HEA.●The formation of reinforcing phases and the self-lubricating effect of graphene collectively enhanced the tribocorrosion resistance of the composite coating.